Perancangan Komik Penjara Masa Depan Bahayanya Narkoba Bagi Remaja - Ridho Sulin Mahendra; Dini Faisal (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The phenomenon of drugs is becoming more and more public figures and famous artists are also involved. This also resulted in the vulnerability of drug issues among adolescents. The lack of attention from teachers and parents is an important problem because it can threaten the lives of the younger generation themselves in the future. To overcome the deviant behavior of the community, the authors created a solution to this problem by presenting a fictitious work about the dangers of drugs for teenagers through creative media, namely the printed comic